PENGARUH JENIS NUTRIENT DAN WAKTU TERHADAP EFISIENSI SUBSTRAT DAN KINETIKA REAKSI FERMENTASI DALAM PRODUKSI BIOETANOL BERBAHAN BAKU BIJI DURIAN - Prahady Susmanto; Yandriani Yandriani; Badria Dania; Ellen Ellen (JURNAL INTEGRASI PROSES, 2020)
Bioethanol is one source of energy that can be obtained from vegetable fermentation. This bioethanol production utilizes durian seed waste as a fermentation media. The purpose of this study was to determine the concentration of urea and NPK and the best time in making bioethanol from durian seeds by Saccharomyces cerevisiae, to study the kinetics of the fermentation reaction, determine the efficiency of the substrate during the fermentation process, and to determine the levels of bioethanol that can be produced from durian seed flour. This research was conducted by adding nutrients in the form of urea and NPK, respectively 3% and 4% with fermentation time for 48, 72, 96, 120, 144, and 168 hours. Based on the research results, the levels of starch contained in durian seed flour were 45.38%. Conversion of starch to sugar by 37,8167 grams. The best substrate efficiency is obtained by urea 3% with 120 hours fermentation time of 99,24% with residual sugar content of 0,76%. The highest levels of bioethanol in the urea sample were obtained at the addition of 3% urea, ethanol content of 57,1429% with a fermentation time of 120 hours and a Vmax of 1,2397 g/mL.hour. The best substrate efficiency obtained in NPK samples was found in NPK 4% fermentation time 144 hours by 99,16% with residual sugar content of 0,84%. The highest levels of bioethanol in NPK samples were obtained by adding 4% NPK, ethanol content of 48,5714% with 144 hours fermentation time and Vmax of 1,0116 g/mL.hour.